Strengthening the military stoic tradition: enhancing resilience in military service members and public safety personnel through functional disconnection and reconnection - McElheran, Megan; Annis, Franklin C.; Duffy, Hanna A.; Chomistek, Tessa (Frontiers in Psychology, 2024)
This paper addresses operational stress injuries (OSIs) among military service members (SM) and public safety personnel (PSP) resulting from prolonged exposure to potentially psychologically traumatic events (PPTEs). While psychotherapeutic interventions for post-traumatic stress injuries (PTSIs) are well established, there is a significant gap in evidence-based mental health training programs addressing proactive mitigation of negative outcomes from PPTEs. Building on the Functional Disconnection/Functional Reconnection (FD/FR) model, we introduce FD/FR 2, emphasizing early identification and management of psychological risks. FD/FR 2 discusses the practice of emotional suppression, or “pseudo-stoicism,” and its potential negative impact on mental health. By integrating authentic Stoic principles, FD/FR 2 offers practical exercises to enhance resilience and well-being, addressing a critical need in current training approaches for military SM and PSP.